Assessment of Streptococcus pneumoniae pilus islet-1 prevalence in carried and transmitted isolates from mother-infant pairs on the Thailand-Burma border. - Turner, P; Melchiorre, S; Moschioni, M; Barocchi, M; Turner, C; Watthanaworawit, W; Kaewcharernnet, N; Nosten, F; Goldblatt, D (2012)
Streptococcus pneumoniae pilus islet-1 (PI-1)-encoded pilus enhances in vitro adhesion to the respiratory epithelium and may contribute to pneumococcal nasopharyngeal colonization and transmission. The pilus subunits are regarded as potential protein vaccine candidates. In this study, we sought to determine PI-1 prevalence in carried pneumococcal isolates and explore its relationship with transmissibility or carriage duration. We studied 896 pneumococcal isolates collected during a longitudinal carriage study that included monthly nasopharyngeal swabbing of 234 infants and their mothers between the ages of 1 and 24 months. These were cultured according to the WHO pneumococcal carriage detection protocol. PI-1 PCR and genotyping by multilocus sequence typing were performed on isolates chosen according to specific carriage and transmission definitions. Overall, 35.2% of the isolates were PI-1-positive, but PI-1 presence was restricted to ten of the 34 serotypes studied and was most frequently associated with serotypes 19F and 23F; 47.5% of transmitted and 43.3% of non-transmitted isolates were PI-1-positive (OR 1.2; 95% CI 0.8-1.7; p 0.4). The duration of first-ever infant pneumococcal carriage was significantly longer with PI-1-positive organisms, but this difference was not significant at the individual serotype level. In conclusion, PI-1 is commonly found in pneumococcal carriage isolates, but does not appear to be associated with pneumococcal transmissibility or carriage duration.